Jakość sosny zwyczajnej, buka zwyczajnego i dębu szypułkowego wyhodowanych z siewu na glebie leśnej o różnym stopniu zagęszczenia - Banach, Jacek; Jaźwiński, Jakub; Kormanek, Mariusz (Leśne Prace Badawcze, 2020)
In this study, we explore the effect of soil compaction on the growth of seedlings of Scots pine Pinus sylvestris L., European beech Fagus sylvatica L. and pedunculate oak Quercus robur L. On the experimental plots, ground contact pressures ranging from 0 to 250 kPa was applied on the soil. The applied pressure resulted in an increase in soil compaction between 1.02 to 1.19 g cm –3 , which reflected pressures exerted by the undercarriage of vehicles used in logging. We then measured the seedlings as well as the dry weight of the roots and the above-ground parts. Using this data, we calculated the following quality indicators for each seedling: SQ – sturdiness quotient, S/R – shoot to root dry mass, DQI – Dickson quality index. For pedunculate oak, the SQ value significantly improved with increasing soil compaction, whereas no differences in the other two indicators were observed. In case of the European beech, the best value of SQ and DQI were observed at a soil density of 1.11 g cm –3 , whilst no significant difference for the S/R coefficient could be found. Completely different results were obtained for Scots pine. The most favorable growth was observed when no pressure was applied. However, the SQ and S/R ratios even exceeded the values commonly considered acceptable. Our results therefore indicate that the values of seedling quality indicators are indeed influenced by soil compaction. At a soil compaction of 1.11 g cm –3 , the share of seedlings with the SQ value below the critical level was the highest, but a similar relationship could not be confirmed for the other indicators. The response of the seedlings to compaction is likely to be species specific.